PROTOTYPE ALAT BEJANA PEMBAKARAN - Sugeng Priyanto (JURNAL KAJIAN TEKNIK MESIN, 2018)
The process of designing a pyrolysis reactor vessel with an electric heating system is intended to design a pyrolysis reactor vessel functioned as a heating chamber for pyrolysis test materials to convert biomass into energy. The vertically-designed torspherical vessel consists of a torispherical shell and head, with a temperature control system designed using a PID control temperature device as its main controller and uses SSR as a voltage controller actuator and uses thermocouple as its temperature sensor and on its heating system using electric heating element. obtained from the test results is the heating rate obtained is 0.25³C / sec with the maximum temperature obtained 480˚C within 30 minutes and the cost required for a single process of Rp 5,500,